A Study Demographic, Histopathological Patterns and Clinical Profile of Oral Squamous Cell Carcinoma in East Java, Indonesia: A Hospital-Based Study - Kania Difa Parama; Nina Irawati; Sunarto Reksoprawiro; Sahudi (HM Publisher, 2021)
Background. Cancer remains a health problem in the world. Estimated 12,7 million new case and 7,6 deaths cause of cancer each year. Oral carcinoma is one of head and neck carcinoma. Oral carcinoma is 6th the most cancer in the world and 90% of the cases are squamous cell carcinoma. The purpose of this research is to study the clinic-epidemiological profile among Indonesian patients associated with oral cancer cases managed in Head and Neck Surgery Unit of Dr Soetomo General Hospital between January 2013- December 2016.Methods. Records of 116 cases were reviewed for clinical details, histopathological data, and follow-up status. Study variables included demographic factor, modifiable risk factors such as tobacco usage and alcohol consumption, site involved, staging, histopathological result, and treatment modalities. Data was presented in form of percentages and proportions.Results. Out of the total 116 cases, majority of the subjects were above 40 years old. Twenty-two (22%) of subjects were young adult (below 40 years old). Seventy-seven subjects (77 %) were male. It was observed that 16 cases (21%) of male subjects was a smoker before they had disease. No female subject consumed tobacco in all form or drinking alcohol. The most common site involved was tongue, followed by lower ginggivo-buccal complex. Histopathologically, 110 cases (95%) was well-differentiated squamous cell carcinoma. Most of the cases (88.8 %) were in advanced stage (stage III or IV) and were treated with surgery followed by adjuvant therapy.Conclusions. The most common site for oral cancer was tongue and majority of the cases were well-differentiated squamous cancer presented in advanced stage of disease. We observed that alcohol consumption and smoking did not have any role in causing oral cancer in women, therefore further study needed to evaluate other possible factors such as diet pattern and oral hygiene. Cigarette smoking might be the cause of oral cancer in male patients.